GRAMMAR IN ARGUMENTATIVE DISCOURSE - Türkan Ali Hasanli (THE USE OF MODERN DIGITAL TECHNOLOGIES IN LINGUISTICS AND FOREIGN LANGUAGE TEACHING. INTERNATIONAL SCIENTIFIC AND PRACTICAL CONFERENCE, 2026)
This article examines the grammatical means that contribute to the verbalization of argumentation within the framework of modern linguistics. The study is primarily based on John Lyons’ Introduction to Theoretical Linguistics, which provides a comprehensive theoretical foundation for analyzing the structural, semantic, and grammatical features of language. The research focuses on how argumentation is not only a semantic process but also a structurally organized grammatical phenomenon. Particular attention is paid to the role of syntactic hierarchy, immediate constituents, and phrase-structure relations in constructing coherent and logically structured arguments. The analysis demonstrates that argumentation relies on the internal organization of sentence structure, where grammatical relations ensure clarity, coherence, and logical progression. In this context, syntagmatic relations are shown to play a key role in expressing cause-effect, contrast, and other logical connections within discourse. Furthermore, the study explores the significance of tense and mood categories in shaping argumentation. Tense is analyzed as a deictic category that situates arguments in relation to the time of utterance, thereby influencing their factual or hypothetical status. Mood, on the other hand, determines the communicative function of the argument, including declarative, interrogative, and imperative forms, each contributing differently to the expression of certainty, obligation, or inquiry. The findings indicate that grammatical structures significantly influence the strength, clarity, and persuasiveness of arguments. Thus, argumentation is not merely a matter of content but also a result of the systematic use of grammatical resources. This study contributes to a deeper understanding of the interaction between grammar and discourse, offering insights into both theoretical linguistics and practical language use.